Economic importance of the Belgian maritime and inland ports - Report 2020 - Ilse Rubbrecht (National Bank of Belgium, 2022)
In 2020, Belgian ports generated exteuro 31.8 billion in direct and indirect value added (7% of Belgian GDP) and employed 254 611 full-time equivalents (FTEs) either directly or indirectly (5.9% of Belgian domestic employment including the self-employed). Despite the COVID-19 outbreak, direct employment at Belgian ports remained quite stable in 2020. The temporary lay-off system - more flexible during the pandemic - played a vital role in avoiding redundancies. Job losses in the port population were especially visible in the non-maritime cluster because the maritime activities were considered as essential and allowed to operate continuously. Direct value added at Belgian ports fell by 1.2% in 2020 against a drop of 4% for the whole of the Belgian economy. The drop was particularly visible in the non-maritime cluster more precisely in those branches hit by the temporary imposed closure of businesses or impacted by demand contractions and supplychain disruptions. In 2020, direct investment by all Belgian ports taken together rose by 5.1% to exteuro 5.1 billion, thanks to higher sums invested in the chemicals industry and the cargo-handling sector. Analysing the investment degree levels by branch of activity, results indicate that shipping companies and port authorities invested relatively more given the competitive businesses in which they operate. A relatively high degree of investment is also notified for the energy sector and the industrial branches, whose operational activity is largely based on high technological knowledge and whose business is substantially subject to future developments. During the pandemic, total turnover figures fell. Downscaling costs to the same extend as declining sales was difficult given the presence of fixed costs, accordingly the profitability level of a median port company declined slowly. However, while strong performing1 port companies in terms of operating profit suffered a drop in profitability, weak performing businesses enhanced theirs owing to the generous government support measures. (In)direct support to wage and (para)fiscal payments endorsed port companies to maintain or even slightly strengthen their liquidity position, while their solvency was sustained as well.
Keywords: C13; C43; C67; C81; J21; J49; L91; L92; R11; R15; R41; 330; Belgian ports; microeconomic data; direct effects; indirect effects; input-output table; employment; value added; investment